Empowering Karangtaruna Of Ngasemlemahbang Village Through Gamelan Training To Preserve Local Culture - Rifky Ardhana Kisno Saputra; Awawin Mustana Rohmah; Zuhro Nurmala M.R; M Najib Alif R.; Miftakhul Jannah (Shof Journal of Social Impact, 2024)
Music is believed to have the power to represent the culture of a person or group at a certain time. He is considered to have a basic understanding of ideas, determining methods and actions in every note produced. The color of sound, range of notes and musical production in each region have many differences. Because in essence, music is a work of art which contains aesthetic symbols from every culture in different societies. Gamelan is a musical instrument that represents or depicts the culture of Javanese society. Some Javanese gamelan in the Surakarta, Yogjakarta and Cirebon palaces include Kyai Guntur Madu, Kyai Guntur Sari, Kyai Naga Wilaga and Gong Sekati. This orchestra has a pentatonic scale in the slendro scale system and pelog scale system. Each gamelan has an honorary name befitting a sacred heirloom. slendro on the gamelan used as the research sample. Meanwhile, the independent variables are the frequency and color of the sound for each area.